O programa Município Verde no território de Paraguaçu Paulista/SP : a estrutura ambiental e as matas ciliares - Moreira, Dimitri Salum (2011)
The environmental issue has gained the best position among the priorities of managers in their areas of government. The fact that he won a big boost in Brazil since 1992, according to the Conference on the Environment "Rio 92," when much was discussed about the global and local environmental issues, with proposals aimed at "sustainable development" had effect on public policies applied to areas in their various scales. With the state government of Sao Paulo was not different, they were undertaken several public policies focused on environmental issues for application in municipal territories. Among these policies highlights the "Projeto Município Verde Azul", in short, is proposing the implementation of guidelines in 10 counties registered in order to their certification with a seal program. Paraguaçu Paulista is one of these cities. The present work is to analyze the municipality of Paulista Paraguaçu two lines before the "Project Green City Blue", directed issue of quality of riparian and environmental structure through the use of "landscape" as an indicator, with the objective of diagnose the state guidelines in both studies. For this was used as the main basis of the proposals and notes by Bertrand & Bertrand (2007) and Passos (2008), plus an extensive survey into the topic.